A simulation study of an innovation‐driven sustainable development model and its impacts and applications: A case study of the Yangtze River Economic Belt. Issue 2 (4th October 2022) - Wang, Wei; Wang, Haofei
Abstract: The economic development process is accompanied by energy consumption and environmental pollution, difficulties which must be overcome to realize sustainable development. A system dynamics model is constructed to simulate the pattern characteristics of an innovation‐driven coupling system scenario for economic development, energy consumption and environmental pollution in the Yangtze River Economic Belt. Then, the impulse response relationship between technological progress and economic, energy and environmental system indexes is further explored by using a vector autoregression (VAR) model. The results show that (1) the model is suitable for predictive analysis. (2) Adjusting the model parameters shows that the innovation‐driven development mode is the optimal sustainable development mode of the Yangtze River Economic Belt. (3) VAR model analysis shows that technological progress has a significant long‐term positive impact on the economic development system index, and the growth of primary industry is the most significant. Technological progress has a significant long‐term inhibition effect on energy consumption and environmental pollution system indicators, among which the inhibition effect on wastewater discharge and power consumption is the strongest. Finally, suggestions are proposed to increase investment in agricultural technology, smart countryside, and wastewater treatment.